1982
DOI: 10.1149/1.2124067
|View full text |Cite
|
Sign up to set email alerts
|

Phase Relationships in Positive Electrodes of High Temperature Li ‐ Al / LiCl ‐ KCl / FeS2 Cells

Abstract: The phases present in FeS2 electrodes operated in normalLiCl‐normalKCl eutectic electrolyte were determined by x‐ray diffraction and by metallographic examination. The phases were FeS2 , KFeS2 , Li3Fe2S4 , Li2.33Fe0.67S2 , Fe1−xS , Li2FeS2 , LiK6Fe24S26normalCl , Li2S , and Fe. The metallographic and crystallographic characteristics of these phases are presented. The sequence of Li‐Fe‐S phases in the FeS2 electrode was in accord with the sequence predicted from the equilibrium Li‐Fe‐S phase diagra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
57
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 0 publications
6
57
0
Order By: Relevance
“…The Li-Fe-S Phase Diagram.- Figure 1 gives the phase diagram for the Li-Fe-S system that is in accordance with Argonne'sl 6 1 data. the positive electrode in equilibrium when the overall composition of the system is within the region.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…The Li-Fe-S Phase Diagram.- Figure 1 gives the phase diagram for the Li-Fe-S system that is in accordance with Argonne'sl 6 1 data. the positive electrode in equilibrium when the overall composition of the system is within the region.…”
Section: Introductionsupporting
confidence: 57%
“…The intermediate phases of the FeS 2 electrode are the subject of some controversy. Tomczuk et a/.1 6 1 at Argonne National Laboratory have accomplished some of the most recent work with this electrode. In their work, the authors summarize the c~mtroversy, and we feel that they also resolve a great deal of it.…”
Section: Introductionmentioning
confidence: 99%
“…For energy storage in lithium batteries, FeS 2 has a theoretical specific capacity of 894 Ah/kg based on the complete conversion of FeS 2 into metallic Fe and Li 2 S. The high specific capacity together with other merits, such as nontoxicity and cost effectiveness, make FeS 2 appealing and competitive in developing the next generation of batteries beyond Li-ion. In particular, the Li/FeS 2 primary battery operating at ambient temperature was already commercialized as early as the 1980's [5], and FeS 2 was proven to be highly reversible in rechargeable lithium batteries operated at high temperatures (375-500 C) [6,7]. Other publications have shown that Li/FeS 2 batteries are capable of being cycled up to 500 cycles in a moderate temperature range of 90-130 C by employing a composite polymer electrolyte [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…12,13 The discharge reaction of FeS 2 as a cathode material in thermal batteries is as given below: FeS 2 + 3 2 Li + + 3 2 e − → 1 2 Li 3 Fe 2 S 4 ("z-phase") [2] However, the high impedance of Li 3 Fe 2 S 4 (the "z-phase"), which is produced in the previous discharge stage, adversely affects its electrochemical properties. 14 In order to reduce the impedances of the electrodes of thermal batteries, new fabrication methods (such as plasma spraying) have been employed to produce FeS 2 cathodes. 15,16 Further, it has been shown in several studies that the electrochemical performance of thermal batteries can be improved slightly by z E-mail: csulzj1208@163.com the addition of conductive carbonaceous materials (including carbon black and carbon nanotubes) to their FeS 2 cathodes.…”
mentioning
confidence: 99%